Challenges of home care: a qualitative study - Mohsen Shahriari; Donya Hafezi Nia; Fatemeh kalij; Maryam Sadat Hashemi (BMC, 2024)
Abstract Background Despite countless benefits of home care, unfortunately, the variety and quality of services provided by homecare centers are uncertain. This study was conducted to explore of home care challenges. Methods The present qualitative study used the content analysis approach. A total of 17 participants, including nurses, managers of home care centers, and patients, were enrolled through purposive sampling. Data were collected using semi-structured interviews and analyzed through Granheim's qualitative content analysis method. Results In order to explain the challenges of home care, after analyzing the data, 700 primary codes, 15 initial categories, sub-subcategories and two main categories, including 'infrastructural challenges' and 'challenges related to the process of home care services provision' emerged. The main category, "infrastructural challenges", consisted of 4 sub-categories (the challenge of acculturalization of home care services, economic challenges of providing services, challenges related to human resources, and the challenge of policymaking and setting regulations and rules for home care). The second main category, "challenges related to the process of home care services provision", consisted of 2 subcategories: challenges of improving the quality of home care services and the challenge of facilities for service provision. Conclusion In order to promote and improve the quality of home care services, in addition to providing insurance coverage for the services, acculturalization and revising the bylaws, empowering the human resource, enhancing the monitoring of the performance of home care centers, and employing modern technology need to be taken into account.